Postclassical Greek contemporary approaches to philology and linguistics - Rafiyenko, Dariya; Seržant, Ilja A. 1977- (Berlin Boston De Gruyter Mouton, 2020)
Frontmatter -- Acknowledgements -- Contents -- Postclassical Greek. An Overview -- Purpose and Result Clauses: ἵνα-hína and ὥστε-hōʹste in the Greek Documentary Papyri of the Roman Period -- Syntactic Factors in the Greek Genitive- Dative Syncretism: The Contribution of New Testament Greek -- Future Periphrases in John Malalas -- Combining Linguistics, Paleography and Papyrology: The Use of the Prepositions eis, prós and epí in Greek Papyri -- Future Forms inPostclassical Greek. Some Remarks on the Septuagint and the New Testament -- Greek Infinitive-Retreat versus Grammaticalization: An Assessment -- Postclassical Greek and Treebanks for a Diachronic Analysis -- The Perfect Paradigm in Theodosius' Κανόνες: Diathetically Indifferent and Diathetically Non-Indifferent Forms -- Forms of the Directive Speech Act: Evidence from Early Ptolemaic Papyri -- What's in a (personal) Name? Morphology and Identity in Jewish Greek Literature in the Hellenistic and Roman Periods -- Confusion of Mood or Phoneme? The Impact of L1 Phonology on Verb Semantics -- Change in Grammatical and Lexical Structures inPostclassical Greek: Local Dialects and Supradialectal Tendencies -- Index
Literaturangaben
[Online-Ausgabe]
Mode of access: Internet via World Wide Web.
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Greek language, Medieval and late; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; FOREIGN LANGUAGE STUDY / General; Grammar of Postclassical Greek; Language Change; Language Contact; Aufsatzsammlung